Caring for migrant and minority patients in European hospitals: a review of effective interventions - Bischoff, Alexander (My University, 2006)
Social changes in European societies place migration and cultural diversity on the European political agenda. The European initiative Migrant Friendly Hospitals (MFH) aims to identify, develop and evaluate models of effective interventions. It has the following objectives: To strengthen the role of hospitals in promoting the health of migrants and ethnic minorities in the European Union and to improve hospital services for these groups. This report reviews models of effective intervention in the medical literature and provides the background information needed to enable partner hospitals taking part in the MFH initiative to select and implement suitable interventions. The interventions reviewed in this study are grouped in four areas: Communication, Responsiveness Empowerment of migrant and minority patients and communities. Monitoring of the health of migrants and minorities and the health care they receive.